Працевлаштування випускників в умовах економічної кризи - Лісогор, Л.С. (Інститут демографії та соціальних досліджень НАН України, 2009)
У статті аналізується специфіка проблем працевлаштування молоді на ринку праці в умовах економічної кризи, визначаються напрями підвищення конкурентоспроможності випускників за рахунок забезпечення відповідності якості освіти вимогам роботодавців. Обґрунтовано необхідність підвищення рівня конкурентності освітніх послуг на основі застосування гнучких моделей навчання. В статье анализируется специфика проблем трудоустройства молодежи на рынке труда в условиях экономического кризиса, определяются направления повышения
конкурентоспособности выпускников за счет обеспечения соответствия качества образования потребностям работодателей. Обосновано необходимость повышения уровня конкурентности образовательных услуг на основе применения гибких моделей образования. The specific features of youth job placement under economic crisis are analyzed at the article. The main trends of graduate’s competitiveness growth on the basis of high quality of education
are defined. The necessity of a providing of competitiveness of education service that foresees using of flexible education models is proved. The significant reasons of complicacy of youth
job placement are analyzed. It’s proved that existing structure of turn-out of specialists doesn’t correspond demand structure. In article the necessity of educational services’ improvement was
argued, and diversification of structure and volume of turn-out of specialists were proposed as an important decision making. As a result of youth job placement’s investigation, the monitoring
mechanism of graduate’s job placement was proposed. It foresees the providing of coordination between education institutions and employers concerning balancing of their interests in graduate’s job placement. The improvement of youth job placement is possible only under conditions of governmental support, improvement of legislative basis, implementation of improved curriculums aimed to adaptation of graduates to labour market demands. The effective measures of educational management system improvement are the creation of conditions for increase of
youth labour market mobility on the basis of progressive technologies of job search.